Interlaminar shear behaviour of hybrid fibre architectures of randomly oriented strands combined with laminate groups. (15th September 2017) - Visweswaraiah, Swaroop B; Lessard, Larry; Hubert, Pascal
Abstract: This work explores the interlaminar shear behaviour of hybrid fibre architectures of randomly oriented strands (ROS) combined with three laminate groups (Cross-ply, Quasi-isotropic and Angle-ply laminates) fabricated using compression moulding. Apparent interlaminar shear strengths of selected configurations are measured. Effects of hybridization on the shear properties of ROS based specimens are quantified and compared with pure ROS and benchmark laminates. Shear strength of hybrid stacking sequence (with laminate groups on either side of a centrally placed ROS group) demonstrate a synergistic effect with higher strengths (up to 25%) than both parent architectures. Negative synergies (up to 20%) are observed due to the sandwiching of laminates in-between two ROS groups. The synergy effects are attributed to the load sharing among the constituents and are explained using a semi-empirical model that utilizes a stochastic strand placement procedure and an adaptation of the analytical formulas for the interlaminar shear and bending stress distributions.